2021
DOI: 10.1177/0095244321996396
|View full text |Cite
|
Sign up to set email alerts
|

Composites based on poly(ethylene-co-vinyl acetate) and silver-calcined scallop shell powder: Mechanical, thermal, photocatalytic, and antibacterial properties

Abstract: Poly(ethylene-co-vinyl acetate) [EVA] and silver-calcined scallop shell powder (Ag-CS) based composite (EVA/Ag-CS) films were synthesized by wet phase inversion method. The composite films were characterized by Fourier transforms infrared spectroscopy (FTIR), X-ray diffraction (XRD) analysis, field emission scanning electron microscopy (FE-SEM), water sorption test, and contact angle measurement. The functional properties such as photocatalytic and antibacterial properties were also studied in detail. Calcined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Active food packaging can migrate nonvolatile components and release volatile compounds into the surroundings of food (Ahmed et al, 2022; Khaneghah et al, 2018; Ozdemir & Floros, 2004; Qian et al, 2021). Therefore, active food packing can maintain food quality, increase food shelf‐life, and enhance food safety Recently, some active food packaging has been developed, such as nanomaterial packaging incorporating metallic nanoparticles, edible coating, and biodegradable packaging (Manoj et al, 2021; Qian et al, 2021). Notably, the functional properties of active packaging materials depend on their active ingredients.…”
Section: Applications Of Calcined Shell Powder In the Food Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…Active food packaging can migrate nonvolatile components and release volatile compounds into the surroundings of food (Ahmed et al, 2022; Khaneghah et al, 2018; Ozdemir & Floros, 2004; Qian et al, 2021). Therefore, active food packing can maintain food quality, increase food shelf‐life, and enhance food safety Recently, some active food packaging has been developed, such as nanomaterial packaging incorporating metallic nanoparticles, edible coating, and biodegradable packaging (Manoj et al, 2021; Qian et al, 2021). Notably, the functional properties of active packaging materials depend on their active ingredients.…”
Section: Applications Of Calcined Shell Powder In the Food Industrymentioning
confidence: 99%
“…The packaging materials that directly contact food should be safe and non‐toxic. Calcined shell powder has received substantial attention because of its strong antimicrobial properties, biocompatibility, and non‐toxicity (Kao et al, 2018; Manoj et al, 2021; Tsou et al, 2019; Wu et al, 2019) Adding calcined shell powder filler to the polymer matrix of food packaging is a great way to prepare composite films (Figure 3).…”
Section: Applications Of Calcined Shell Powder In the Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Nanosilver antibacterial agents have been added to a variety of polymer materials in the past research, and the antibacterial properties of the composites show great differences. [25][26][27] Interestingly, some researchers have reported that silver exhibits different antibacterial properties in different materials. Lin et al 28 found that the antibacterial efficiency of PET/Ag was higher than that of PP/Ag with the same silver content in the composite.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the three possible antibacterial mechanisms of nano‐silver: (1) binding to cell membranes, membrane proteins, and DNA bases leading to disruption of normal function; (2) release of silver ions, affecting membranes, DNA and proteins; (3) generate reactive oxidative species (ROS), which may also affect DNA, cell membranes and membrane proteins 23,24 . Nanosilver antibacterial agents have been added to a variety of polymer materials in the past research, and the antibacterial properties of the composites show great differences 25–27 . Interestingly, some researchers have reported that silver exhibits different antibacterial properties in different materials.…”
Section: Introductionmentioning
confidence: 99%